Perencanaan Produksi Cairan Pembersih Dengan Metode Rata-rata Bergerak dan Pemulusan Eksponensial - Ruspendi; Rusmalah; Patria Adhistian (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2024)
Laboratories that are quite productive in designing and developing products that have been made and marketed on an internal scale include floor cleaning liquid, hand washing liquid and dish washing liquid. It's just that most of the products are produced based on customer orders or make to order. So when there are orders in large quantities, customers have to wait a little, between two and three days, because cleaning fluid products have to be produced first. The estimated need for Handsoap products is 49 liters, floor cleaning fluid is around 75 liters, dishwashing liquid is estimated at 81 liters by testing the forecasting method, the forecasting method that should be used as a basis for decision making is used to estimate the need for Handsoap products using the 4-month moving average method. The forecasting method for estimating the need for floor cleaning fluid products is the exponential smoothing method ? = 0.2. And the forecasting method for estimating the need for dishwashing liquid products is the exponential smoothing method ? = 0.2 which has a relatively smaller error value compared to other models.